Mothering in the context of intimate partner violence: A feminist intersectional critique of the nursing literature. (4th October 2022) - Broughton, Sharon; Ford‐Gilboe, Marilyn; Varcoe, Colleen
Abstract: Aims: To describe how mothers and mothering in the context of IPV are conceptualized in the nursing research and practice literature with attention to underlying ideologies, biases and potential harms. Design: Feminist intersectionality was used as a theoretical and analytic lens. Data Sources: Articles published between 2000 and 2021 in the nursing literature, identified by searching Google Scholar, CINAHL, PubMed and Scopus databases, and conducting bibliographic reviews of published articles. Review Methods: Search terms included: intimate partner violence, domestic violence, parenting, mother and nursing. Initial screening resulted in inclusion of 98 papers for analysis. Results: Four dominant ways of conceptualizing mothering in the context of IPV were identified: (1) IPV is conceptualized as a discrete acute event and/or crisis, (2) mothering is treated as a practice, (3) mothers are valued as vehicles for child health and well‐being and (4) mothers are seen as vulnerable and 'at risk'. These narrow constructions are rooted in ideologies such as normative motherhood, deficit and grit/resilience and neoliberalism. Emerging shifts in the literature are providing an important counter‐balance. Conclusion: Biases in nursing knowledge about mothering in the context of IPV may limit nursing's capacity to support the health of these women and their children. The integration of emerging perspectives that emphasize strengths and equity is critical in strengthening nursing knowledge and practice and in beginning to redress existing limitations and potential harms. Impact: This critique focused on higher‐income countries of the Global North but raises fundamental questions that should be considered in other contexts. Applying broader conceptualizations of mothers, mothering and IPV to research and practice can help improve the quality of care available.